The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0138551
|View full text |Cite
|
Sign up to set email alerts
|

Focal Ischemic Injury with Complex Middle Cerebral Artery in Stroke-Prone Spontaneously Hypertensive Rats with Loss-Of-Function in NADPH Oxidases

Abstract: By means of introgressing a loss-of-function mutation in the p22phox gene from the Matsumoto Eosinophilia Shinshu (MES) rat to stroke-prone spontaneously hypertensive rats (SHRSP), we constructed the SHRSP-based congenic strain lacking the P22PHOX expression (i.e., lacking NADPH oxidases [NOX] activities) (SHRSP.MES-Cyba mes/Izm; hereafter referred to as SP.MES). To examine the effects of Nox activities on the focal ischemic injury or stroke, we performed middle cerebral artery (MCA) occlusion in this new cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…S3b and ref. 7). Since P22PHOX is an essential subunit of the active NOX, the ROS level was expected to be low in SP.MES, and indeed, DHE staining (see below for the method) showed a lower level of superoxide in RVLM in SP.MES (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3b and ref. 7). Since P22PHOX is an essential subunit of the active NOX, the ROS level was expected to be low in SP.MES, and indeed, DHE staining (see below for the method) showed a lower level of superoxide in RVLM in SP.MES (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To examine this hypothesis, we introduced a P22PHOX-depleted congenic SHRSP, which was recently developed in our laboratory7. This congenic strain (called as SP.MES) was established to harbor the null mutation in the P22phox gene of the Matsumoto Eosinophilic Shinshu rat (MES)8.…”
mentioning
confidence: 99%
“…Because Nox1-4 need to form heterodimers with the membrane-bound p22 phox subunit [ 1 ], SP.MES lacks Nox activities on the background of the SHRSP. Although we have reported the results of photothrombotic distal MCAO in this new congenic strain [ 73 ], the findings are summarized below.…”
Section: Experimental Models Of Strokementioning
confidence: 99%
“…Physiological variables such as blood pressure are critically important in experimental stroke; for example, congenic removal of a blood pressure quantitative trait locus (decreased blood pressure by 12% or −29 mmHg) attenuated infarct size produced by MCAO [ 70 ]. Our previous study mentioned above showed slightly but significantly decreased blood pressure in SP.MES (i.e., Nox dysfunction due to the absence of p22 phox protein) when compared with SHRSP/PM0, suggesting that decreased levels of resting or pre-stroke blood pressure in hypertensive rats would attenuate infarct size produced by MCAO [ 73 ]. Therefore, decreases in blood pressure due to the absence of p22 phox may explain at least in part the protective effects against focal ischemic injury observed in SP.MES.…”
Section: Experimental Models Of Strokementioning
confidence: 99%